2015
DOI: 10.1126/science.aaa1356
|View full text |Cite
|
Sign up to set email alerts
|

A Werner syndrome stem cell model unveils heterochromatin alterations as a driver of human aging

Abstract: Werner syndrome (WS) is a premature aging disorder caused by WRN protein deficiency. Here, we report on the generation of a human WS model in human embryonic stem cells (ESCs). Differentiation of WRN-null ESCs to mesenchymal stem cells (MSCs) recapitulates features of premature cellular aging, a global loss of H3K9me3, and changes in heterochromatin architecture. We show that WRN associates with heterochromatin proteins SUV39H1 and HP1α and nuclear lamina-heterochromatin anchoring protein LAP2β. Targeted knock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
513
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 470 publications
(549 citation statements)
references
References 47 publications
23
513
2
3
Order By: Relevance
“…We next investigated whether the metformin‐Nrf2‐GPx7 pathway also functions in HMSCs. We observed that the expression levels of Nrf2 and GPx7 decreased in both replicative senescent HMSCs and premature senescent HMSCs (Werner syndrome‐specific: WRN ‐deficient) (Li et al., 2016; Zhang et al., 2015) (Figure 5a). High levels of GPx7 were also observed in HMSCs genetically bearing an endogenous NRF2 nucleotide variation (A254G, referred to as HMSC‐ NRF2 AG/AG ) (Yang et al., 2017) (Figure 5b), which encodes a constitutively activated Nrf2 protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated whether the metformin‐Nrf2‐GPx7 pathway also functions in HMSCs. We observed that the expression levels of Nrf2 and GPx7 decreased in both replicative senescent HMSCs and premature senescent HMSCs (Werner syndrome‐specific: WRN ‐deficient) (Li et al., 2016; Zhang et al., 2015) (Figure 5a). High levels of GPx7 were also observed in HMSCs genetically bearing an endogenous NRF2 nucleotide variation (A254G, referred to as HMSC‐ NRF2 AG/AG ) (Yang et al., 2017) (Figure 5b), which encodes a constitutively activated Nrf2 protein (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The ligand‐based target list for metformin also contained several chromatin‐modifying epigenetic regulators including lysine‐specific demethylases 4A (KDM4A) and 4C (KDM4C), Jumonji 2 proteins that demethylate di‐ and trimethylated histone 3 lysine 9 (H3K9me2/3) and H3K36me3, two epigenetic markers closely related to the aging process (Sen et al., 2015; Zhang et al., 2015). Moreover, when the default similarity score of 0.8 used for ligand‐based VP was reduced to 0.65–0.7, a number of histone lysine demethylases including KDM2A, KDM5A/C, KDM4B/D/E, KDM7, KDM5C, KDM6A/UTX, KDM6B/JMJD3, and LSD1 (KDM1A) emerged as new putative targets of metformin.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, mutations in LMNA and ZMPSTE24 in patients lead to metabolic dysfunction, including type 2 diabetes and hepatic steatosis (Galant et al., 2016; Shackleton et al., 2000). Moreover, a recent report has implicated disorganization of heterochromatin at the lamina as a driver of human aging (Zhang et al., 2015). Numerous enzymes associated with H3K9me3, the mark associated with heterochromatin, including acetyltransferases (SRC‐1/ Ncoa1 ), deacetylases (Hdac3), methyltransferases (Suv39 h1 and G9a/ Ehmt2 ), and demethylases (Jhmdh2a/Kdm3a, Jmjd2c/Kdm4c), have been linked to fatty liver, diabetes, and obesity (Picard et al., 2002; Sun et al., 2012; Tateishi et al., 2009; Wang et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A recent report implicated disorganization of heterochromatin at the lamina as a driver of human aging (Zhang et al., 2015). Mutations in LMNA , encoding the nuclear structural protein lamin A/C, result in disturbed nuclear architecture and cause the premature aging syndrome Hutchinson‐Gilford progeria (HGPS).…”
Section: Introductionmentioning
confidence: 99%